Analisis Faktor-faktor Penyusutan Susu Sapi Untuk Meminimalkan Kerugian (Studi Kasus pada Koperasi Unit Desa Mandiri Bayongbong, Kabupaten Garut) - Jaka Sudewa (IKOPIN, 2020)
The existence of depreciation of cow's milk makes the cooperative must bear the costs of depreciation, because every depreciation of milk has become a purchase cost. Depreciation of cow's milk affects the business results achieved by the Mandiri Bayongbong KUD dairy business unit, the amount of depreciation reduces the volume of milk sales to IPS and the amount of business results generated by the dairy business unit. Depreciation can be overcome by carrying out quality control as an appropriate control mechanism towards improving quality. The method used in this research is the case study method, which is one of the descriptive research methods. Where used direct observation techniques (observation) of the object under study with the use of cause and effect diagrams, why analysis tables and pareto diagrams as research analysis aids. The sampling technique uses the strata method based on the ownership of cattle on a business scale with the number of productive female livestock. Then obtained the following sample values: n1 = 9 people, n2 = 9 and n3 = 17 people. The results showed that the amount of shrinkage of cow's milk was 3,736 liters or 0.77% due to poor quality milk, broken or damaged, left in a shelter or spilled / scattered when depositing milk in the TPK or IPS. After using the Pareto diagram, the factors that cause the most influential problems are the materials, equipment, methods, and enclosures.